2020
DOI: 10.1186/s13031-020-00267-z
|View full text |Cite
|
Sign up to set email alerts
|

Displacement-related factors influencing marital practices and associated intimate partner violence risk among Somali refugees in Dollo Ado, Ethiopia: a qualitative study

Abstract: Background: Child and forced marriage have negative health consequences including increased risk of intimate partner violence (IPV) for women and girls. War and humanitarian crises may impact decision-making around marriage and risks of IPV for displaced populations. A qualitative study was conducted among Somali refugees in Dollo Ado, Ethiopia to understand the interplay of factors that contribute to IPV and to inform an intervention. This secondary analysis aims to explore the influence of displacement on ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…In some cases, early and forced marriage can be seen as a coping and survival strategy for families facing financial hardship due to conflict (Sharma et al, 2020). Conflict can result in increased barriers to education, separation of families, and increased poverty which leads to changes in relationships and marital practices including early marriages (Schlecht et al, 2013).…”
Section: Sexual and Gender-based Violence During Conflictmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, early and forced marriage can be seen as a coping and survival strategy for families facing financial hardship due to conflict (Sharma et al, 2020). Conflict can result in increased barriers to education, separation of families, and increased poverty which leads to changes in relationships and marital practices including early marriages (Schlecht et al, 2013).…”
Section: Sexual and Gender-based Violence During Conflictmentioning
confidence: 99%
“…Early marriage can be also perceived to be a means of keeping daughters safe and protecting them from poverty and sexual violence in countries of refuge (Abraham and Tastsoglou, 2016). In some cases, early marriage can also be adopted as a weapon of war (Sharma et al, 2020). Armed groups may force girls to marry combatants, and abduct girls for this purpose (Human Rights Watch, 2012).…”
Section: Sexual and Gender-based Violence During Conflictmentioning
confidence: 99%
“…Indeed, a recent study in Dolo Odo by Sharma et al found evidence for perceived changes in child marriage which were attributed to "NGO awareness-raising programs and Ethiopian laws prohibiting child marriage as well as increased access to education for girls." [38] Nonetheless, the low rates can in part be due to underestimation of child marriage prevalence among 15-19-year-old girls due to right censoring as well as potential underreporting stemming from social desirability bias. That the practice was still less frequently reported among 18-and 19-year-old women who completed time at risk of child marriage compared to older women suggests that right censoring is not entirely the reason behind the low rates.…”
Section: Discussionmentioning
confidence: 99%
“…In the Lebanese context, poor socio-economic conditions and fear for girl's safety has led some families to marry their daughters off at a younger age [15]. Those girls marrying young, and particularly those with older spouses, can be at increased risk of intimate partner violence [26][27][28]. Restrictions to education and a lack of safety make them dependent on men, resulting in a lack of agency and the continued presence of patriarchal pressures associated with child marriage [7,15].…”
Section: The Experience Of Adolescent Syrian Girls Displaced In Lebanonmentioning
confidence: 99%